A study on the relationship between factors of physical environment comfort and employees job performance at Majlis Bandaraya Kuala Terengganu / Nurul Syakira Mahammad - Mahammad, Nurul Syakira (Faculty of Business & Management, 2017)
The purpose of this study is to measure the relationship between physical environment comfort and employees' job performance at Majlis Bandaraya Kuala Terengganu (MBKT) located in Kuala Terengganu. This study also needs to identify which physical environment comfort factors that most influence the employees' job performance. Besides that, this study uses to identify the current problem faced by the employees from physical environment comfort toward their job performance. This study was conducted among the employees in three departments in the organization and the questionnaires have been distributed to all departments in the departments. The total population of this study was about 40 employees and 36 of them were took part as a respondents in answering the questionnaires. Through the findings, ergonomic office equipment factor is the most significant factor of physical environment comfort that affect employees' job performance while the least significant factor was noise. Several recommendations were suggested in order to make some improvement to the employees' job performance at Majlis Bandaraya Kuala Terengganu.